Bilateral deafness, diabetes, and different types of cardiomyopathy in family members with m.3243A > g mutation: a case report. Issue 2 (15th February 2023) - Seiler, Florian; Ruile, Philipp; Moser, Martin; Helbing, Thomas
Abstract: Background: The point mutation at position 3243 in the mitochondrial MT-TL1 gene (m.3243A > G) is a rare cause of hypertrophic cardiomyopathy (HCM). Information about HCM progression over time and occurrence of different cardiomyopathies in m.3243A > G carriers of the same family is still lacking. Case summary: A 48-year-old male patient was admitted to a tertiary care hospital with chest pain and dyspnoea. Bilateral hearing loss required hearing aids at the age of 40. A short PQ interval, narrow QRS complex, and inverted T-waves in lateral leads were present on the electrocardiogram. HbA1c of 7.3 mmol/L indicated prediabetes. Echocardiography excluded valvular heart disease and detected non-obstructive HCM with slightly reduced left ventricular ejection fraction (48%). Coronary artery disease was ruled out by coronary angiography. Myocardial fibrosis determined by repeated cardiac MRI progressed over time. Endomyocardial biopsy excluded storage disease, Fabry disease, and infiltrative and inflammatory cardiac disease. Genetic testing revealed m.3243A > G mutation in the MT-TL1 gene associated with mitochondrial disease. Clinical evaluation and genetic testing of the patients' family revealed five genotype-positive relatives with heterogeneous clinical phenotypes including deafness, diabetes mellitus, kidney disease, and both hypertrophic and dilated cardiomyopathy. Discussion: In patients with unexplained symmetric HCM with heterogenic clinical phenotypes at the organ levels, mitochondrial disease should be taken into consideration, particularly in the context of matrilinear transmission. m.3243A > G mutation is associated with mitochondrial disease in the index patient and five family members and leads to the diagnosis of maternally inherited diabetes and deafness with intra-familial variability of different cardiomyopathy forms.